Pengaruh Kualiatas Layanan dan Store Atmosphere Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Sebagai Variabel Intervening (Studi Kasus Pada Konsumen di Restoran Toean Watiman Yogyakarta) - Henny Welsa; Muhamad Khoironi (EBBANK, 2019)
The purpose of this study was to describe the relationship between Service Quality, Store Atmosphere, and Purchasing Decision. The population is restaurant customer Toean Watiman Yogyakrta. The sample used in this study were 100 respondents. While the data analysis technique uses multiple regression analysis techniques and path analysis.The results showed that service quality has a significant positive effect on purchasing decisions, store atmosphere has a significant positive effect on purchasing decisions, service quality has a significant positive effect on customer satisfaction, store atmosphere has a significant positive effect on customer satisfaction, purchasing decisions have a significant positive effect on customer satisfaction, quality service and store atmosphere together have a significant positive effect on customer satisfaction through purchasing decisions with the results of the calculation of 137.768> 3.09 and the significance of 0.000 <0.05. service quality and store atmosphere have a significant positive effect on purchasing decisions with a count of 101,693 with a significance of 0,000 <α 5%